Electroluminescence studies of modulation p-doped quantum dot laser structures - Hasbullah, Nurul Fadzlin; Hopkinson, Mark; Alexander, Ryan R.; Hogg, Richard A.; David, John P.R; Badcock, Tom J.; Mowbray, David J. (IEEE, 2010)
Electroluminescence (EL) measurements have been performed on InAs/InGaAs/GaAs quantum dot (QD) structures with varying amounts of modulation p-doping. Temperature-dependent EL measurements show a reduction of the integrated EL intensity (IEL) with increasing temperature but with the size of this reduction decreasing with increasing doping level. An increase in the activation energy controlling the EL quenching is found with increasing p-doping. This is attributed to an increased coulombic attraction between the extrinsic holes and injected electrons. At room temperature and low injection current, a superlinear dependence of the IEL on the injection current is observed. This superlinearity decreases as the p-doping increases and this behavior indicates a reduction in the amount of nonradiative recombination. This reduction is believed to be caused by the saturation of nonradiative centers and/or reduced escape of electrons to the GaAs barrier due to the increased confinement potential.